ESTIMATION OF MAXIMUM SUSTAINABLE HARVEST LEVELS OF SEA CATFISHES IN SINDH, PAKISTAN - M. Noman; Y. T. Mu; S. Abbas; M. Mohsin; A. Mehak (Journal of Animal and Plant Sciences, 2018)
It is necessary to access fishery stock status before harvesting due to continued overexploitation of fishery resources. The aim of this study is to estimate maximum sustainable yield (MSY) of sea catfishes (Family: Ariidae) in Pakistani marine waters from Sindh coastline. Research method used is the statistical analysis of fishery output (FO) and fishery input (FI) data by using non-equilibrium surplus production models ( SPMs). In Catch and Effort Data Analysis (CEDA) software, three SPMs viz. Fox model (F-M) , Schaefer model (S-M) and Pella-Tomlinson model (PT-M) were used along with three error assumptions (EAs) viz. log ( L-EA) , log normal (LN-EA) and gamma (G-EA). Whereas, in A Stock Production Model Incorporating Covariates (ASPIC) computer package two SPMs viz. Fox (F-M) and Logistic (L-M) were employed for data analysis. For initial proportion ( IP) 0.9, CEDA software computed MSY in range 12,000 2 16,000 t ( metric ton) . F-M showed the highest goodness of fit (R = 0.928) value. For the same IP value, ASPIC computer 2 package estimated MSY in a range 14,000 20,000 t. Here, F-M again showed higher R (0.926), value. Estimated results suggest that, MSY range at Sindh coast is around 12,000 200,000 t. However, FO statistics indicate that this resource has consistently been overexploited. The conclusion of this study is that this fishery resource is overharvested and demand some concrete fishery management steps for its conservation in Pakistani marine waters. ( Schaefer, 1954; Pella and Tomlinson, 1969; Fox, 1970;
Keywords: Sea catfishes; MSY; CEDA; ASPIC; Sindh; Pakistan.